Mainstreaming Blue-Green Infrastructure - Ranadive, Suruchi; Shah, Purva (Calibrating Urban Livability in the Global South, 2024)
India’s coastline is increasingly becoming vulnerable to climate change. Over the years, extreme climate change events such as floods, uneven rainfall and storm surges are becoming common around several coasts. These environmental changes will impede the social, cultural and economic patterns of the coasts. Moreover, partly inefficient disaster management and lack of mitigation and adaptation plans escalate the vulnerability of coastal communities. Coastal cities need to adopt an urban planning approach that can cope with these uncertainties. The paper seeks to understand the concept of ecological infrastructure as a planning tool to combat climate change impact in urban areas. It investigates the benefits of blue-green infrastructure (BGI) against the grey infrastructure used conventionally to manage services in cities. The paper explores design application of BGI through cases demonstrated in literature review around BGI. It also understands the challenges it faces and the opportunities it offers. The research underlines the importance of placemaking as a tool for effective management and sustainability of BGI. The conclusions drawn from this study, are applied to a design proposal prepared by the author’s team as a part of competition entry. The paper suggests few amendments and improvements from international best practices around BGI.